2012
DOI: 10.3892/etm.2012.567
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-based metabolomic analysis for identifying serum biomarkers to evaluate methotrexate treatment in patients with early rheumatoid arthritis

Abstract: Abstract. To identify the major serum biomarkers predicting the response to methotrexate (MTX) treatment in patients with early rheumatoid arthritis (RA), we evaluated the relationships between the individual response to MTX and various associated factors utilizing the 1 H nuclear magnetic resonance ( 1 H NMR)-based metabolomic method. Thirty-eight early RA patients were enrolled in this cohort study, and they received MTX (10 mg/week) orally as monotherapy for 24 weeks. According to the American College of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 28 publications
5
59
2
Order By: Relevance
“…Of note, recent metabolic phenotyping of atherosclerotic plaques showed perturbations in acylcarnitine metabolism which the authors suggest is related to dysregulation of fatty acid metabolism and mitochondrial dysfunction [93••]. Wang et al reported serum NMR-based metabolomics analysis on patients with early RA treated with methotrexate (the goldstandard DMARD) and showed that the patients could be grouped into those that benefitted from the drug and those that did not [94]. Our group has also shown that baseline 1 H NMR urine metabolic profiles discriminated between RA patients who did or did not have a good response to TNF therapy with a sensitivity of 88.9 % and a specificity of 85.7 % [95].…”
Section: Metabolomics In Ramentioning
confidence: 98%
“…Of note, recent metabolic phenotyping of atherosclerotic plaques showed perturbations in acylcarnitine metabolism which the authors suggest is related to dysregulation of fatty acid metabolism and mitochondrial dysfunction [93••]. Wang et al reported serum NMR-based metabolomics analysis on patients with early RA treated with methotrexate (the goldstandard DMARD) and showed that the patients could be grouped into those that benefitted from the drug and those that did not [94]. Our group has also shown that baseline 1 H NMR urine metabolic profiles discriminated between RA patients who did or did not have a good response to TNF therapy with a sensitivity of 88.9 % and a specificity of 85.7 % [95].…”
Section: Metabolomics In Ramentioning
confidence: 98%
“…In one study 103 , a 1 H-NMR metabolomic approach was applied to 38 patients with active RA. After 24 weeks, patients who responded to methotrexate treatment showed significant elevations in serum levels of uric acid, taurine, methionine, glycine, histidine and hypoxanthine, and reductions in levels of uracil, TMAO, α-oxoglutarate, aspartate, and tryptophan, compared with patients in whom methotrexate was not effective 103 .…”
Section: Metabolomic Studies In Rheumatic Diseasementioning
confidence: 99%
“…In one study 103 , a 1 H-NMR metabolomic approach was applied to 38 patients with active RA. After 24 weeks, patients who responded to methotrexate treatment showed significant elevations in serum levels of uric acid, taurine, methionine, glycine, histidine and hypoxanthine, and reductions in levels of uracil, TMAO, α-oxoglutarate, aspartate, and tryptophan, compared with patients in whom methotrexate was not effective 103 . NMR analysis of urine from 16 patients with RA and 20 with psoriasis (before anti-TNF therapy) 104 identified upregulation of histamine, glutamine, phenylacetic acid, xanthine, xanthurenic acid and creatinine, and downregulation of ethanolamine, p-hydroxyphenylpyruvic acid and phosphocreatine in samples from patients who had a good response to therapy.…”
Section: Metabolomic Studies In Rheumatic Diseasementioning
confidence: 99%
“…RA is a type of chronic and systemic autoimmune disease that is characterized by erosive joint synovitis, which harms body systems and organs, such as joints, the heart and the kidney (11). RA attacks facet joints symmetrically, for instance, articulationes digitorum manus, articulationes digitorum pedis and wrist joints (12).…”
Section: Discussionmentioning
confidence: 99%